Music-based interventions for pain relief in patients undergoing hemodialysis: A PRISMA-compliant systematic review and meta-analysis - Cheng, Jingru (Medicine (Baltimore), 2021)
BACKGROUND: Music therapy and music-based interventions have been used widely in numerous medical procedures to reduce the physical and psychological disorders. However, the effect of music therapy on pain relief in hemodialysis patients still remains unclear. METHODS: Electronic databases were comprehensively searched through MEDLINE, Web of Science, EMBASE, Cochrane, and WANFANG. All studies met inclusion criteria were eligible for systematic review and meta-analysis. Clinical variables were extracted and pooled results were obtained using STATA software. RESULTS: A total of 10 studies with 722 participants were included for systematic review. Overall, music therapy showed a significantly favorable effect on reducing pain for patients undergoing hemodialysis (SMD: −0.90, 95%CIs: −1.25 to −0.55, P < .001). No publication bias was observed. CONCLUSIONS: Music-based interventions could significantly relieve pain for patients undergoing hemodialysis, which should be promoted as an effective and safe complementary method.